Beyond the Symbol: A Ground-Breaking Study of the Portrait of Francysk Skaryna - Shutova, Olga (Senoji Lietuvos literatūra, 2020)
Илья Лемешкин, Портрет Франциска Скорины. К 550-летию со дня рождения книгоиздателя = Ilja Lemeškinas, Pranciškaus Skorinos Portretas. 550-ąsias gimimo metines minint = Il’ja Lemeškin, Portrait de Francisk Skorina. En commémorant le 550e anniversaire de sa naissance, (1470–2020), (The Portrait of Francysk Skaryna. To mark the 550th anniversary [1470–2020] of the publisher), (Travaux du Cercle linguistique de Prague, nouvelle série, vol. 10), Vilnius–Prague: Institut national de langue lituanienne / Cercle linguistique de Prague, 2020, 298 p. ISBN 978-609-411-266-9 / ISBN 978-80-87269-58-9